Personal Branding Guru Agama Kristen - Martina Labora Nainggolan; Putra Rajagukguk; Marthalena Lumbangaol; Eniwati Nduru; Rainaldi Setiawan; Hisardo Sitorus (Jurnal Riset Rumpun Ilmu Bahasa, 2026)
The development of modern education demands that teachers play a broader role beyond merely delivering subject matter, including building professional reputation, credibility, and positive influence on students, colleagues, parents, and society. For Christian Religious Education teachers, personal branding has a deeper dimension because they also serve as role models and ambassadors of Christian values. This study aims to describe the formation of personal branding among Christian Religious Education teachers based on spiritual and theological values, as well as its impact on teaching and student character development. The method used is descriptive qualitative through a literature study of books, journals, notes, and relevant reports, with narrative analysis to illustrate the practices and values that shape teachers’ personal branding. The findings indicate that the personal branding of Christian Religious Education teachers is an integration of professional competence, personal integrity, and Christian values, encompassing authenticity, consistency, professionalism, spiritual and moral role modeling, inspirational and communicative abilities, adaptation to technology, and positive relationships with students and the community. Spiritual and theological values such as Christian love, integrity, humility, patience, justice, service, and commitment to God’s Word form the main foundation that strengthens teachers’ credibility, motivates students, and establishes them as living examples of Christian life. Personal branding for Christian Religious Education teachers is not merely an image or popularity, but a real reflection of faith, character, and daily behavior consistent with Christian teachings, thus supporting effective learning, student character formation, and the teacher’s reputation as an authentic, inspiring, and professional educator.